Autonomy Necessary but not Sufficient: Comparative Study of CFM, Nepal and JFM, India - Chate, Rucha; Ghate, Suresh (Journal of Forest and Livelihood, 2013)
‘Autonomy’ to local users is widely discussed and considered a necessary attribute to form and effectively function self-governing associations in common pool resources. Especially when the resource is local in scale, autonomy to local users can ensure good governance on the ground so locals are better equipped in developing effective institutions. This article compares varying degrees of autonomy to forest dwelling communities and its effect in decentralized forest management in two countries – Nepal and India. Comparison is made by using data collected from revisits of 6 IFRI sites from each country, after creating indices for functional autonomy, institutional functioning, forest quality, and forest dependence of the respective communities. The paper concludes that extending autonomy to communities is not enough; rather autonomy needs to be functional. Also, forming and putting institutions in place may not lead to improvement in forest quality and forest product availability. The newly created institutions need sufficient investment to make them robust, for which positive and proactive intervention by various agencies is essential. DOI: http://dx.doi.org/10.3126/jfl.v9i1.8592 Journal of Forestry and Livelihood Vol.9(1) 2010 33-44